2016
DOI: 10.1016/j.yjmcc.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Peptidase inhibitor 16 is a membrane-tethered regulator of chemerin processing in the myocardium

Abstract: A key response of the myocardium to stress is the secretion of factors with paracrine or endocrine function. Intriguing in this respect is peptidase inhibitor 16 (PI16), a member of the CAP family of proteins which we found to be highly upregulated in cardiac disease. Up to this point, the mechanism of action and physiological function of PI16 remained elusive. Here, we show that PI16 is predominantly expressed by cardiac fibroblasts, which expose PI16 to the interstitium via a glycophosphatidylinositol (-GPI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 24 publications
(36 reference statements)
3
50
3
Order By: Relevance
“…chemerin and MMP2 9,11 . PI16 has been described to inhibit the proteolytic activation of the chemoattractant chemerin 9,11 . However, we did not detect any difference in the expression of precursor- and activated-chemerin in the lumbar DRGs between WT and Pi16−/− post SNI (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…chemerin and MMP2 9,11 . PI16 has been described to inhibit the proteolytic activation of the chemoattractant chemerin 9,11 . However, we did not detect any difference in the expression of precursor- and activated-chemerin in the lumbar DRGs between WT and Pi16−/− post SNI (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified two possible targets of PI16 that could contribute to changes in leukocyte migration/infiltration, i.e. chemerin and MMP2 9,11 . PI16 has been described to inhibit the proteolytic activation of the chemoattractant chemerin 9,11 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations